Microbial Applications Vol.2 2017
DOI: 10.1007/978-3-319-52669-0_2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Source of Melatonin and Its Clinical Aspects

Abstract: Melatonin chemically known as N-acetyl-5-methoxytryptamine is a small physiological compound of diversified functions. Melatonin has been found in phylogenetically different taxa of bacteria, unicellular eukaryote, microalgae, plants, fungi, and animals. Identification of melatonin in many of these microorganisms is missing, and its function is rarely known. Although, melatonin in microorganisms is not essentially involved in circadian process, rather, it exhibits antioxidant property also and may protect chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 83 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Moreover, several clinical studies demonstrated that the ingestion of melatonin produces a reduction in the toxicity of chemotherapeutic agents in cancer patients (Palmer et al 2020). On the other hand, experimental models on rats showed that melatonin delays tumorigenesis initiation since interactions with DNA-bound carcinogens prevent the accumulation of mutations inside cells and the initiation of cancer (Kumar et al 2017). Melatonin has also the ability to repair cellular damage and protect healthy cells (Kumar et al 2017).…”
Section: Accepted Articlementioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, several clinical studies demonstrated that the ingestion of melatonin produces a reduction in the toxicity of chemotherapeutic agents in cancer patients (Palmer et al 2020). On the other hand, experimental models on rats showed that melatonin delays tumorigenesis initiation since interactions with DNA-bound carcinogens prevent the accumulation of mutations inside cells and the initiation of cancer (Kumar et al 2017). Melatonin has also the ability to repair cellular damage and protect healthy cells (Kumar et al 2017).…”
Section: Accepted Articlementioning
confidence: 99%
“…On the other hand, experimental models on rats showed that melatonin delays tumorigenesis initiation since interactions with DNA-bound carcinogens prevent the accumulation of mutations inside cells and the initiation of cancer (Kumar et al 2017). Melatonin has also the ability to repair cellular damage and protect healthy cells (Kumar et al 2017). Tamtaji et al (2019) reviewed the results of several in vivo and in vitro studies claiming that supplementation with melatonin showed a therapeutic alternative for pancreatic cancer.…”
Section: Accepted Articlementioning
confidence: 99%
See 3 more Smart Citations